Curva de Phillips: uma construção para o Brasil (2002 – 2013) - Silva, Bruno dos Santos (2015)
The relationship between inflation and unemployment, called the Phillips curve was used by several economies since 1960 as a key theoretical tool for the development of economic policies. The pioneering study by AW Phillips developed an empirical analysis with data on unemployment and change in wages in the UK, found a tradeoff between the variables, which enabled the economic policy makers choose between a low unemployment with high inflation and high unemployment with low inflation. However, in the 1970s, the theory of the Phillips Curve was put in check because of stagflation, the presence of high rates of inflation and unemployment. The changes in the economic scenario caused changes in the generation of socioeconomic data. Thus, the Phillips theory underwent theoretical changes over the years in order to further pursue its explanatory power. Given the above, the question arises whether the applicability of the Phillips curve is still appropriate for today's economies. This study estimated a Phillips curve for the Brazilian economy in the 2002-2013 period, using an econometric approach. The analysis consisted in the use of time series, by means of co-integration technique for data on inflation, unemployment in that period. The results, considering the variables applied, show that it was not possible to verify an inverse relationship between inflation and unemployment in Brazil during the study period. It is intended in future work to add more variables to the model in order to get Phillips curve estimates for Brazil more significant.